216 PREVENTING PEDIATRIC FIREARM FATALITY IN MILES CITY, MONTANA. Issue 1 (1st January 2007) - Chan, A.
Abstract : Purpose of Study: Firearms account for 10% of all fatality among children aged 5 to 14 in the United States. Surveys reveal that a relatively high percentage of Miles City, MT, adults (12.8%) keep unlocked, loaded firearms in the home compared with the national average (7.6%). The goal of this project was to prevent pediatric firearm fatality in Miles City by increasing the use of trigger locks and teaching children to avoid firearms. Methods: Public health nurses and the police department were consulted, the latter providing 100 free trigger locks. A literature search was conducted to review prominent firearm-avoidance curricula. Results: A session was held at a local children's summer program of approximately 40 children ages 5 to 11, in which a speaker taught the children widely accepted steps to take in the event of a firearm encounter: stop, don't touch, leave the area, and tell an adult. The lesson was then reinforced in the form of a game in which the children acted out the steps after encountering a fake firearm. Trigger locks were distributed to each child to pass on to his or her parents. Conclusion: The session was enthusiastically received and most children seemed to comprehend it. Although no follow-up assessments of the children's skills or trigger lock use were performed, it can be hoped that at least some of the children learned the lesson and at least some of their parents will take steps to ensure their safety.